2012
DOI: 10.1111/j.1532-950x.2012.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Ureters in Dogs: Clinical Features, Surgical Techniques and Outcome

Abstract: The prognosis after surgery is fair with a success rate of 72% and a complication rate of 26%. Resection of only the intravesicular ectopic ureter resulted in resolution of incontinence in a high percentage of dogs and thus is an acceptable alternative to removal of the entire ureteral remnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
1
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(118 citation statements)
references
References 33 publications
5
95
1
17
Order By: Relevance
“…In the study of Reicher et al [2] related with EU cases, they indicated early start of UI, observation of a higher incidence of left unilateral EU and that urethra shaping of urethral opening is usually more common in females than in males; and the data were consistent with the data of our case.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the study of Reicher et al [2] related with EU cases, they indicated early start of UI, observation of a higher incidence of left unilateral EU and that urethra shaping of urethral opening is usually more common in females than in males; and the data were consistent with the data of our case.…”
Section: Discussionsupporting
confidence: 82%
“…Suspected bladder and urethral functional anomalies, such as USMI, have been reported in 75 to 89 percent of female dogs [5] and the most common clinical sign associated with EU was UTI [2] . Dilatation of the renal pelvis and hydroureter may be associated with maldevelopment of structures or acquired infection [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though continuous or intermittent urinary incontinence is reported as primary complaint since birth in the history [5] , urinary incontinence is generally continuous character in EU patients [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Different neoureterostomy techniques have been developed, especially for the treatment of intramural EU [13,18,19] . The primary objective of these studies is to minimize the presence of postoperative incontinence.…”
Section: Introductionmentioning
confidence: 99%